Anthropological foundations of public health; the case of COVID 19 - Hahn, Robert A. (Prev Med Rep, 2021)
OBJECTIVES: The complex societal spread of COVID-19 in the U.S. indicates a need to recognize sociocultural forces to best understand and respond to the pandemic. This essay describes four principles of anthropology and sister disciplines that underlie the theory and practice of public health. METHODS: Research following anthropological and related approaches is reviewed to provide examples of the four principles from COVID-19 in the U.S. RESULTS: 1. What counts as sickness, disease, injury, pathology, is fundamentally a matter of historically situated social ideas and values. 2. The ways in which societies are organized is a fundamental source of pathologies and their distributions within societies. 3. Conversely, health conditions can substantially alter the organization of societies. 4. Public health responses are social processes that affect intervention outcomes. CONCLUSIONS: Anthropological approaches are recommended to address several facets of public health practice: problem analysis, intervention design, evaluation, and the public health enterprise itself.